2021
DOI: 10.1038/s43247-021-00301-9
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl-richness controls organic carbon preservation during coprecipitation with iron (oxyhydr)oxides in the natural environment

Abstract: The coprecipitation of organic carbon with iron minerals is important for its preservation in soils and sediments, but the mechanisms for carbon-iron interactions and thus the controls on organic carbon cycling are far from understood. Here we coprecipitate carboxylic acids with iron (oxyhydr)oxide ferrihydrite and use near-edge X-ray absorption fine structure spectroscopy and wet chemical treatments to determine the relationship between sequestration mechanism and organic carbon stability against its release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 83 publications
9
48
0
Order By: Relevance
“…4b). These results are in line with other studies (Chen et al 2014;Fisher et al 2020;Curti et al 2021), suggesting that alkyl C, O-alkyl C, and carboxylic C were associated with glomalin-Fe co-precipitation. Eusterhues et al (2011) found that polysaccharide-rich DOM is mainly responsible for adsorption of reactive Fe, while aromatic C is mainly associated with the Fe co-precipitation (Eusterhues et al 2011).…”
Section: Fe-associated Grsp Chemistry In Mangrove Soilssupporting
confidence: 93%
“…4b). These results are in line with other studies (Chen et al 2014;Fisher et al 2020;Curti et al 2021), suggesting that alkyl C, O-alkyl C, and carboxylic C were associated with glomalin-Fe co-precipitation. Eusterhues et al (2011) found that polysaccharide-rich DOM is mainly responsible for adsorption of reactive Fe, while aromatic C is mainly associated with the Fe co-precipitation (Eusterhues et al 2011).…”
Section: Fe-associated Grsp Chemistry In Mangrove Soilssupporting
confidence: 93%
“…Eight Fh organomineral coprecipitates with different wt%C were prepared with three simple carboxylic acids following the method of Curti et al (2021). The acids were denoted as acidn/m, where acid refers to the first three letters of the acid IUPAC name and n/m denotes the number of carboxyl groups (n) and the number of total carbon atoms (m).…”
Section: Preparation Of Fh Organomineral Coprecipitatesmentioning
confidence: 99%
“…Because of this they play a dominant role in OC sequestration mechanisms and thus in the long-term accumulation of OC in soil (Kramer et al, 2012). Spectroscopic studies using Fouriertransform infrared spectroscopy (FTIR) and near edge X-ray absorption fine structure spectroscopy (NEXAFS) provide direct evidence for carboxylate-Fe bonds forming via a ligand exchange mechanism between carboxyl functional groups and Fe minerals (Chen et al, 2014;Chorover and Amistadi, 2001;Curti et al, 2021;Gu et al, 1994;Hall et al, 2020;Kaiser and Guggenberger, 2007;Kaiser et al, 1997;Lv et al, 2016;Solomon et al, 2005;Zeng et al, 2020). Recent NEXFAS spectroscopy however, also shows that as the number of carboxyl functional groups present in simple carboxylic OC compounds increases, the number of carboxylate-Fe bonds formed between the carboxyl functional groups and the Fh particles increases, and thus the binding strength, stability and persistence of the OC associated with Fh also increases (Curti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Fe­(III)-stabilizing ligands induce a high spin iron electron configuration , and are typically comprised of low molecular weight acids, which include functional groups rich in oxygen, (carboxylates, catecholates, hydroxymates, and phenolates), , sulfur (cysteine, thiol), , and nitrogen (porphyrins) . Some strong ligands, such as nitrilotriacetic acid (NTA) and ethylenediaminetetraacetic acid (EDTA) have both oxygen and nitrogen components. ,, Fe­(II)-stabilizing ligands, such as ferrozine and phenanthroline, are known to have bipyridyl moieties in their structure and contain only N ligating atoms and induce low spin iron. ,, Recent studies have either modeled or experimentally determined that the majority of Fe­(II) complexed to DOM binds to carboxylate and phenolate groups due to their abundance in DOM.…”
Section: Introductionmentioning
confidence: 99%